Constitutionality of the new immediate process - Araya Vega, Alfredo G. (2016)
The new process aims to provide an immediate solution to regulatory problems of citizen insecurity perceived in Peru. A differentiated and prompt attention for crimes committed in flagrancy and the increase of the delinquencies incidence, omission of family support and drunk driving is proposed. The study of this new procedure should cover the main criticism, to a weighting of constitutionality.